AB0218 FUNCTIONAL DISABILITY AND PAIN BUT NOT DISEASE ACTIVITY ARE ASSOCIATED WITH POOR HEALTH-RELATED QUALITY OF LIFE IN A COHORT OF RHEUMATOID ARTHRITIS PATIENTS. (2nd June 2020) - Prata, A. R.; Assunção, H.; Luis, M.; Brites, L.; Costa, F.; Dinis de Freitas, J.; Silva, S.; Da Silva, J. A. P.; Duarte, C.
Abstract : Background: Rheumatoid Arthritis (RA) is a systemic autoimmune disease that presents with joint pain and inflammation leading to significant disability and poor health-related quality of life (HRQoL) (1, 2). Optimizing long-term HRQoL is the primary goal of disease management in RA (3). Objectives: To evaluate HRQoL and identify its influencing clinical and demographic factors in a Portuguese RA population. Methods: This is a cross-sectional study including consecutive patients fulfilling the ACR/EULAR 2010 and/or ACR 1987 RA classification criteria, followed at a tertiary Rheumatology Department. Sociodemographic and clinical variables were collected. HRQoL was assessed using the EuroQoL 5-Dimensional Descriptive System (EQ-5D) total score (normal range from -0.496 to 1.000, lower values indicating poorer HRQoL). Independent t-test and Pearson's correlation coefficient were performed to evaluate EQ-5D differences between groups and examine its relationships with continuous variables, respectively. Variables with p<0.1 in univariate analysis were included in a stepwise multiple linear regression analysis to evaluate the independent association of variables with the EQ-5D score. Results: 358 RA patients were included (80.20% female, mean age ± SD: 63.22 ± 0.66 years old). Mean EQ5D total score ±SD was 0.48 ± 0.01. Based on EQ-5D domains, 0.60% reported extreme problems with mobility, 3.40% extreme problems with self-care, 2.50% extreme problems with usual activities, 12.0% extreme pain or discomfort, and 7.30% extreme anxiety or depression symptoms (Fig. 1). There was a significant difference in EQ-5D scores between male (M=0.55, SD=0.24) and female gender (M=0.46, SD= 0.27); t (356) = -2.41, p=0.016. EQ-5D was weakly correlated with DAS-28-CRP (r=-0.32; p<0.001), moderately correlated with patient's global assessment of disease activity (r=-0.54; p<0.001) and pain-visual analogue scale (pain-VAS) scores (r=-0.58; p<0.001) and strongly with Health Assessment Questionnaire (HAQ) score (r=-0.72; p< 0.001). After multivariate analysis, HAQ-score (β=-0.57 [95% CI -0.24 to -0.17]; p<0.001) and pain-VAS ((β=-0.25 [95% CI -0.003 to -0.002]; p<0.001) remained as independent predictors of EQ-5D (R2=0.56, p<0.001). Conclusion: Greater functional impairment and pain are associated with poor HRQoL in RA patients, and thus special attention must be given to treatment strategies providing the best patient-centred outcomes. References: [1]Yaghoubi et al. J Cardiovasc Thorac Res 2012;4(4):95–101. [2]José E et al. Ann Rheum Dis 2018;1118–24. [3]Smolen JS et al. Ann Rheum Dis. 2010; 69:631–637 Disclosure of Interests: Ana Rita Prata: None declared, Helena Assunção: None declared, Mariana Luis: None declared, Luisa Brites: None declared, Flavio Costa: None declared, João Dinis de Freitas: None declared, Stefanie Silva: None declared, José Antonio P. da Silva Grant/research support from: Pfizer, Abbvie, Consultant of: Pfizer, AbbVie, Roche, Lilly, Novartis, Catia Duarte: None declared